Efficacy and safety of Prunella vulgaris L. combined with antithyroid drugs for hyperthyroidism: a systematic review and meta-analysis - Wei, Maoying; Zhao, Qiyao; Yuan, Mingyi; Fan, Yuyun; Li, Mingdi (Frontiers in Pharmacology, 2025)
ObjectiveTo systematically evaluate the efficacy and safety of Prunella vulgaris L. (PVL) preparations combined with antithyroid drugs (ATDs) for the treatment of hyperthyroidism.MethodsEight Chinese and English databases were searched for randomized controlled trials (RCTs) comparing PVL preparations combined with ATDs and ATDs for hyperthyroidism treatment. The Cochrane risk-of-bias assessment tool was used to evaluate the quality of included studies. Statistical analyses were performed using the Revman 5.3 software. Stata software (version 16.0) was used to detect publication bias. The GRADE system was used to assess the level of evidence.ResultsSeventeen studies were analyzed. The total sample size was 1,366 patients. Meta-analysis revealed that treatment with PVL preparations in combination with ATDs effectively reduced free triiodothyronine [standardized mean difference (SMD) = −0.98, 95%CI (−1.39, −0.57), P < 0.00001], free thyroxine [SMD = −0.82, 95% confidence interval (CI) (−1.16, −0.47), P < 0.00001], thyrotropin receptor antibody [SMD = −1.11, 95%CI (−1.52, −0.71), P < 0.00001], thyroid isthmus thickness [mean difference (MD) = −0.13, 95%CI (−0.15, −0.10), P < 0.00001], width of left thyroid lobe [MD = −0.22, 95%CI (−0.27, −0.17), P < 0.00001], thickness of left thyroid lobe [MD = - 0.22, 95%CI (−0.33, −0.10), P = 0.0003], length of left thyroid lobe [MD = −0.63, 95%CI (−0.79, −0.47), P < 0.00001], width of right thyroid lobe [MD = −0.21, 95%CI (−0.26, −0.16), P < 0.00001], thickness of right thyroid lobe [MD = −0.27, 95%CI (−0.32, −0.22), P < 0.00001], length of right thyroid lobe [MD = −0.45, 95%CI (−0.61, −0.28), P < 0.00001], incidence of adverse events [risk ratio (RR) = 0.34, 95%CI (0.24, 0.50), P < 0.00001], tumor necrosis factor-α [SMD = −2.05, 95%CI (−2.85, −1.25), P < 0.00001], and increasing thyroid-stimulating hormone [SMD = 0.71, 95%CI (0.43, 0.99), P < 0.00001], and interleukin-10 [MD = 1.73, 95%CI (1.35, 2.10), P < 0.00001] better than that of ATDs alone. Combination therapy with PVL preparations was comparable to the efficacy of ATDs alone in improving relapse rates and interleukin-6 and interferon gamma levels.ConclusionTreatment of hyperthyroidism with PVL preparations in combination with ATDs was superior to treatment with ATDs alone in terms of improvements in thyroid function, thyroid antibodies, thyroid gland size, inflammation, and incidence of adverse events. However, owing to the low strength of evidence from the included studies, this conclusion requires further validation in more high-quality RCTs.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024572591.